Triangulation of family perspectives on father-adolescent talk about sex and relationships - Grossman, Jennifer M.; DiMarco, Audrey J.; Richer, Amanda M. (Frontiers in Developmental Psychology, 2024)
Father-adolescent talk about sex can protect adolescents from sexual risk behaviors. However, few studies explore how family members view fathers' talk with adolescents about sex and relationships. An understanding of how fathers, mothers, and adolescents view fathers' roles in talk with adolescents about sex and relationships can help to guide fathers' talk with adolescents and inform programs to provide targeted support for father-adolescent communication about sex and relationships. This study investigates family perceptions of father-adolescent communication about sex and relationships by triangulating data from fathers, mothers, and adolescents using content analysis to conduct between-family analysis and within-family approaches with 15 families (n=45 individuals) with high school-aged adolescents from across the U.S. Analyses showed agreement on the importance of fathers' roles in family talk about sex. The findings showed shared recognition of the importance of fathers' roles in family talk about sex. Betweengroup analyses showed that fathers, mothers, and adolescents view fathers' roles as emotional supports and open communicators with their adolescents about sex and relationships and as educators and advisors for their adolescent children. Within-family analysis showed that families often agreed that there were gender differences in how fathers talked with their sons and daughters, but family members expressed different views on how adolescents' gender impacts father-adolescent communication about sexual topics. These findings may encourage fathers who are uncertain about the value of their roles in talking with their adolescent children about sex and relationships. They also highlight the importance of examining how fathers' messages to their adolescents about sex and relationships may continue to follow patterns of gender stereotypes. This is the first study to qualitatively triangulate perspectives of fathers, mothers, and adolescents on father-adolescent communication about sex and relationships. Since fathers are often less involved than mothers in parent-adolescent communication about sex and relationships, an understanding of how mothers and adolescents see fathers' roles and messages can help provide a pathway for fathers' engagement which works within a family system.